Інтраопераційне гістологічне експрес-дослідження щитоподібної та прищитоподібних залоз - Шаповал, Н. О.; Хоперія, В. Г.; Гирявенко, О. Я.; Золотарьов, П. О. (Clinical Endocrinology and Endocrine Surgery, 2010)
This review presents and analyzes the results of numerous clinical studies on the problems of intraoperative frozen section of tumors of the thyroid and parathyroid glands.